Shipping a year in review - Lazaro, Cheche (Quezon City Probe Productions, 1988)
A look at shipping in the Philippines after the Dona Paz tragedy, considered the worst mantime disaster after Titanic. The episode looks at what has been done about the problems facing the industry.
VHS.
Keywords: Shipping -- Philippines; Shipwrecks -- Philippines; Survival after airplane accidents, shipwrecks, etc